Dampak Kurang Tidur akibat Begadang terhadap Fungsi Kognitif dan Konsentrasi pada Mahasiswa - Rosna Madelu; Muh. Wahyuddin S. Adam; Antris Pakaya; Meris Lapasatu; Nandi Arsyandi (Lembaga Pengembangan Kinerja Dosen, 2025)
Sleep quality and quantity play a crucial role in maintaining students' cognitive functions and concentration. This article aims to examine the impact of staying up late (sleep deprivation) on students’ concentration and cognitive performance using a qualitative approach through literature review. The findings reveal that frequent sleep deprivation negatively affects the immune system, memory, focus, and emotional stability. Blue light exposure from electronic devices, academic stress, and unhealthy lifestyles further exacerbate sleep disturbances. Students with poor sleep patterns tend to experience reduced motivation and lower academic achievement. Therefore, raising awareness about the importance of sufficient sleep is essential to support academic success and mental health.